Retrospective observational study about patient friendly and cost effective wound care by newer concept of open dressing - Mane, Arun Y.; Naik, Narendra G. (International Surgery Journal, 2019)
Background: The choice of dressing material and to give wound cover varies according to the type of ulcer and the surgeon’s experience. It is practically not possible to do comparative evaluation among different types of dressing material and method to dress. The ideal dressing material and method to dress must be cost effective, comfortable to patient and early wound healing with minimal sequel of scar tissue. The article discusses about a newer method cost effective and patient friendly dressing to achieve effective end result in wound healing. Methods: Retrospective analysis of 50 patients treated from 01 April 2019 to 31 August 2019 by open dressing with written informed consent of patient and fulfilling ethical requirements at Rajiv Gandhi Medical College, Thane, Mumbai. The selection criteria of patients were cases with pressure dressing are excluded. The diabetic (40%), venous (20%) and traumatic (20%) ulcers are selected. Results: Out of 50 cases, in 76% sample cases ulcer healed by secondary intention without skin grafting. It was noticed better early improved status of the ulcer by excellent granulation tissue and without deterioration in status of large ulcers (24%), operated for skin grafting. The concept of covering wound by washed cotton cloth after regular wound wash, antiseptic ointment, and adjuvant conservative therapy, helped to improve patient’s comfort during outpatient department visit and inpatient department stay. Conclusions: It concludes that the newer concept of wound cover by washed cotton cloth is patient friendly and cost effective without compromising the status of wound healing.